Penerapan Metode House Of Risk (HOR) dalam Upaya Mengurangi Potensi Kecelakaan Kerja di Area Produksi Gasket - Hake Indriyanto Pratama; Andarmadi Jati Abdhi Wasesa (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
This study aims to identify the potential risk of work accidents, determine the main causative factors, and develop risk mitigation strategies using the House of Risk (HOR) method in the gasket production area at PT XY. This research is motivated by the high potential for work accidents caused by the use of production machines, especially press machines that are not equipped with safety systems, as well as the implementation of risk management that still needs to be improved. The research uses a quantitative descriptive method by collecting data through direct observation and interviews with parties involved in the production process. The analysis was carried out using HOR Phase I to identify and determine the priority of risk agents based on the Aggregate Risk Potential (ARP) value, then continued with HOR Phase II to determine the most effective mitigation actions. The results of the study showed that there were 10 risk events and 14 risk agents that had the potential to cause work accidents. The main causative factors include high production targets, reduced operator concentration, machines without safety guards, non-compliance with SOPs, less than optimal preventive maintenance, damaged electrical cables, and inconsistent use of personal protective equipment (PPE). Prioritized mitigation strategies include increasing compliance with the use of PPE, implementing regular preventive maintenance, strengthening the implementation of SOPs through routine inspections, Occupational Safety and Health (K3) training, implementing the 5R/5S program, and installing safety sensors on press machines. The application of the HOR method provides a systematic approach in determining risk control priorities so that it can improve work safety in the production area.